Упростить выражение
(x+2)(5x-1)-x(9+x)
Решите уравнение
7(2у-2)-2(3у-3,5)=9

Melisaaaa Melisaaaa    1   30.10.2020 10:26    0

Ответы
danilp18 danilp18  29.11.2020 10:26

вот ответ от вас накожу


Упростить выражение (x+2)(5x-1)-x(9+x) Решите уравнение 7(2у-2)-2(3у-3,5)=9
Упростить выражение (x+2)(5x-1)-x(9+x) Решите уравнение 7(2у-2)-2(3у-3,5)=9
Упростить выражение (x+2)(5x-1)-x(9+x) Решите уравнение 7(2у-2)-2(3у-3,5)=9
ПОКАЗАТЬ ОТВЕТЫ
Catania2 Catania2  29.11.2020 10:26

На фото все расписала


Упростить выражение (x+2)(5x-1)-x(9+x) Решите уравнение 7(2у-2)-2(3у-3,5)=9
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра